Elimination of palatoradicular groove: a combined endo-perio effort (Bangladesh Journal of Medical Science, 2014)
Palatoradicular groove is an anomaly which is found more frequently in upper lateral and central incisors. This condition may lead to endo-perio lesions. A 19- year- old female presented with chief complaint of swelling and pus discharge from the gums of the right side of the upper front teeth and she also complained of loose tooth and intermittent pain. On clinical examination, probing pocket depth of 10 mm, grade II mobility and extrusion of the tooth was found. A combined endo-perio treatment was performed and elimination of the groove, pain and reduction in probing pocket depth and mobility was achieved. The purpose of this case is to highlight an interdisciplinary approach towards the management of an anomaly which may affect the endodontic status of the tooth and periodontal health of the patient. DOI: http://dx.doi.org/10.3329/bjms.v13i3.15216 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.345-349